2015
DOI: 10.1021/acs.jpcc.5b06273
|View full text |Cite
|
Sign up to set email alerts
|

Nanometer-Size Polyoxometalate Anions Adsorb Strongly on Neutral Soft Surfaces

Abstract: Polyoxometalates (POMs) are nanometric metal-oxide anions with unique chemical and physical properties. During last decade, significant efforts have been made to give POMs surface activity and self-assembly properties that are essential for catalysis applications and for producing organic-inorganic hybrid materials. In this work, POMs based surfactants are produced spontaneously through non-covalent interactions in water by mixing non-ionic surfactants with POM. The most common POMs of tungstosilicate and tung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
173
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 107 publications
(186 citation statements)
references
References 43 publications
(95 reference statements)
11
173
0
2
Order By: Relevance
“…In a previous study it was shown by SAXS that addition of salts, such as NaCl, to POM aqueous solutions leads to the screening of electrostatic repulsions between the POM anions . A salt induced screening effect was also previously observed between non‐ionic micelles decorated by POMs .…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…In a previous study it was shown by SAXS that addition of salts, such as NaCl, to POM aqueous solutions leads to the screening of electrostatic repulsions between the POM anions . A salt induced screening effect was also previously observed between non‐ionic micelles decorated by POMs .…”
Section: Resultsmentioning
confidence: 82%
“…In a previous study it was shown by SAXS that addition of salts, such as NaCl, to POM aqueous solutions leads to the screening of electrostatic repulsions between the POM anions . A salt induced screening effect was also previously observed between non‐ionic micelles decorated by POMs . In the following, the screening of electrostatic repulsions in the PW–(EO) x mixtures was investigated for a fixed PW concentration of 25 m m by adding 100 m m NaCl, which is sufficient to screen most of the electrostatic repulsions.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…[PW 12 O 40 ] 3− , q/M=0.25; [P 2 W 18 O 62 ] 6− , q/M=0.33), während die Nb V ‐Spezies [Nb 6 O 19 ] 8− größere q/M‐Verhältnise (hier: 1.33) aufweisen. Zusammengefasst bilden POMs also so genannte chaotrope Anionen, die das Wasserstoffbrückennetz in wässriger Lösung unterbrechen und so zum Ausfällen von Makromolekülen wie Polymeren, neutralen Tensiden und Proteinen führen. Entsprechend ist wegen der Anwendungsbreite von POMs auf die Solvatationsenergien von POM und Kation zu achten, weil das Wechselspiel zwischen Solvatationsenergie und Gitterbildungsenergie des entsprechenden POM‐Kation‐Salzes die Löslichkeit der Spezies kontrolliert.…”
Section: Einleitung: Grundlagen Der Pom‐kation‐wechselwirkungenunclassified